2010
DOI: 10.1136/jme.2009.033142
|View full text |Cite
|
Sign up to set email alerts
|

Ethics committees for biomedical research in some African emerging countries: which establishment for which independence? A comparison with the USA and Canada

Abstract: The process of establishing ethics committees could affect their functioning and compromise their independence in some African countries and in North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Four studies described the history of African RECs (Henderson et al, 2007; Kass et al, 2007; Oyedeji, 2011; Rwabihama, Girre, & Duguet, 2010). A survey of 20 African RECs reported that 9 countries had established RECs in the 1980s, whereas the other 11 were created during the period 1995 to 2003 (Rwabihama et al, 2010). South Africa, with the oldest REC in Africa, had its first REC established at the University of Witwatersrand in 1967.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies described the history of African RECs (Henderson et al, 2007; Kass et al, 2007; Oyedeji, 2011; Rwabihama, Girre, & Duguet, 2010). A survey of 20 African RECs reported that 9 countries had established RECs in the 1980s, whereas the other 11 were created during the period 1995 to 2003 (Rwabihama et al, 2010). South Africa, with the oldest REC in Africa, had its first REC established at the University of Witwatersrand in 1967.…”
Section: Resultsmentioning
confidence: 99%
“…South Africa, with the oldest REC in Africa, had its first REC established at the University of Witwatersrand in 1967. The Medical Research Council in Zimbabwe was established soon thereafter in 1974 (Kass et al, 2007; Rwabihama et al, 2010). The National Health Sciences Research Committee of Malawi was established in 1988 (Henderson et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Opponents of CEC and moral expertise may essentially be objecting to the idea of people who profess to have the right answer in moral situations, because: (1) they hold that there is no such objectively verifiable thing, and (2) this society respects and protects autonomous moral decision-making more highly than correct moral decision-making. Rwabihama et al ( 2010 ). Ethics committees for biomedical research in some African emerging countries: Which establishment for which independence?…”
Section: Methodsmentioning
confidence: 99%
“…Although biomedical research involving human subjects has been conducted in Africa for more than half a century, most ethics committees on the continent were created in the 2000s (Rwabihama et al, 2010). Many committees were initially established with the primary objective of reviewing international research in which both the sponsoring and hosting countries were required to review the research protocol before commencement of the research project (Rwabihama et al, 2010). Furthermore, many IRBs in Africa now have Federal Wide Assurances (FWAs), a contractual assurance with the US federal government, and an indication that institutions have likely received US research funds or have collaborated with US-funded researchers.…”
Section: Introductionmentioning
confidence: 99%